Universal Design for Learning in Action: Exploring Strategies, Outcomes, and Challenges in Inclusive Education - Catama, Bryan V (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
Despite strong global advocacy for inclusive education, a gap persists between policy  and classroom practice. Universal Design for Learning (UDL) offers a proactive  framework to address learner diversity, but its implementation remains uneven.  This narrative review examined UDL applications in inclusive education from  2014 to 2024, focusing on instructional strategies, academic and social outcomes,  and implementation challenges. A structured search of Consensus and Researcher. Life databases identified empirical studies published in English during the review  period. Studies were included if they presented original data on UDL strategies,  outcomes, or barriers within formal school or university settings. Eight studies met  the inclusion criteria. Findings show that UDL-based instruction frequently applies  multiple modes of engagement, representation, and expression. Digital platforms  often support access and personalization. Reported outcomes include improved  motivation, academic engagement, and social inclusion, although impact varies  based on implementation quality and institutional support. Key challenges involve  limited training, inadequate resources, and inconsistent understanding of UDL  principles. This review affirms UDL’s potential as an equity-driven framework  for inclusive education. However, its success depends on sustained investment  in professional development, strong leadership, and policy alignment to enable  systemic adoption.
Keywords: Universal Design for Learning (UDL); inclusive education; instructional design; accessibility in education; differentiated instruction; educational equity; teacher professional development; inclusive pedagogy